The larvae of Beraeamyia aphyrte Malicky 1972, Beraeamyia kutsaftikii Malicky 1975, and Beraeamyia matsakii Malicky 1980 (Trichoptera: Beraeidae), including a discriminatory matrix to the Greek Beraeidae larvae - Waringer, Johann; Malicky, Hans (Zootaxa, 2018)
This paper describes the previously unknown larvae of three Beraeidae species restricted to Greece: Beraeamyia aphyrte Malicky 1972, Bm. kutsaftikii Malicky 1975, and Bm. matsakii Malicky 1980 (Trichoptera: Beraeidae). Information on the morphology of the larvae is given, and the most important diagnostic features are illustrated. The trio of species can be easily separated by an angle present in the dorsal outline of the pronotal carina in Bm. kutsaftikii whereas this dorsal outline is straight in the remaining two species. Finally, the dorsal ridge of the pronotal carina touches the dorsal ecdysial line in Bm. matsakii, but fades far away from the ecdysial line in Bm. aphyrte. With respect to distribution, Bm. kutsaftikii is restricted to the mountains of Central Greece, the Peloponnesos, and the island of Euboea; Bm. matsakii is an endemic of the Ochi mountains in the southern part of Euboea and the island of Andros; and Bm. aphyrte is an endemic of the island of Crete. The species are integrated in a synoptic discriminatory matrix including the currently known Greek Beraeidae larvae. In addition, ecological information on the species is provided.